PEMBUATAN MESIN PEMERAS, JAHE UNTUK INDUSTRI KECIL KOPI , JAHE BUBUK - Darmono, Darmono (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2004)
The  voucher  program   entitled  "Manufacturing    Ginger  Squeezer  Machine  for Small  Powder   Ginger-Coffee    Industries"   aims  to  increase   productivity   of  the  UD. ROSE  KURNIA   especially   in  squeezing  basic  material  of ginger  as a substance  for Powder  Ginger-Coffee   and  Coconut   Sugar  Ginger  being  produced.   It also  wants  to know the suitable  size and productivity  of such ginger squeezer  machine.,         The   steps   of  this   manufacturing    ginger   squeezer    machine    are   planning, machine  manufacturing,   and training  for industry  partner  workers.  The  planning  step includes:  (1) designing  machine  plan  draft,  (2) calculating   the needed  materials,  and (3)  calculating   the  implementation    cost.  The  machine-manufacturing     step  includes: (1)  material   cutting  to  fit  the  work  draft,  (2)  welding,   (3)  assembling,   (4)  electric installation.   (5) machine  performance   test,  and (6) painting.  The training  for industry partner  workers   consists   of:  (1)  theory   and  speech  delivery,   (2)  demonstration    of machine using, and (3) machine  using practice  by the industry  partner  workers.The result  of the  voucher  program  is realization  of a squeezer  ginger  machine and skill  achievement   by the  industry  partner  workers  in the  machine  operation.  The squeezer  ginger  machine   was  made  of right-angled   iron  frame  sizing  50x50x5  mm, combined   with  plywood   of  3 mm  and  12 mm  thick.  The  machine   size  is  120 em length,  60 em width,  and  190 em height,  moved  by a gasoline  motor  power  HONDA of 4 HP  and rotation  speed  of  1400 RP;-'1, The  crushing  system  runs  by 2 cylindrical tubes   with   20   em   diameter    rotating    in   the   opposite    direction.    The   machine performance   and productivity   for  squeezing   ginger  has  speed  of  4 to  5 times  faster compared  with manual  squeezing  system having  been done up   till now.Key words:  ginger   squeezer  machine,  and small  powder   ginger-coffee   industry.